POLA HUBUNGAN EKSEKUTIF - LEGISLATIF DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN MOJOKERTO TAHUN 2020 - Anggie Parawitha Lucca (Journal Publicuho, 2022)
If the relationship between the two Executive and Legislative States Institutions is not managed properly, it will create a disharmonious relationship. The executive and legislative bodies are mandated by law to draft regulations, including Regional Regulations (Perda) related to the Regional Revenue and Expenditure Budget (APBD). Mojokerto Regency, one of the regions in the 2020 fiscal year, went through quite heated APBD discussions due to the absence of common ground between the DPRD and the Regional Government. As a result, efforts to accelerate APBD documents, which are expected to be completed before the end of November, are slow. The APBD document was finally carried out at the end of the month, November 30th. The research method used is descriptive qualitative research. The data collected is obtained through observation, literature study, archives/documents, or written literature related to the research title. The study results found that the pattern of relationships formed between the DPRD and the Mojokerto Regency Government in the preparation of the 2021 APBD tends to be Legislative Heavy, where the dominance of the DPRD is prominent. This can be due to the executive’s low political support because a temporary official leads Mojokerto Regency during the 2021 APBD preparation process. (Pjs) so that he does not have a representative power in the DPRD.